Plan of the Nah-whit-ti Indian Reserves, Rupert District ... - Surveyor General Of British Columbia (University of Victoria Libraries, 2023)
Surveyed and drawn by E.M. Skinner, no date. [Signed by P. O'Reilly, Indian Reserve Commissioner.] [Approved by F.G. Vernon, Chief Commissioner for Lands and Works, 18 May 1889.] Map showing Reserves in the areas around Queen Charlotte Sound including Hope Island Reserve No. 1; Semach Reserve No. 2; Ouchtum Reserve No. 3; Nah-Witti Reserve No. 4; and Clen-Cla-Ouch Reserve No. 5 on Balaclava Island. ...